Hematological indicators of liver damage during the subclinical phase of fasciolosis in steers from Northeastern Argentina - Coppo, J. A. (2010)
The aim of this study was to determine eventual changes in blood parameters that characterize liver damage during the subclinical phase (asymptomatic) of liver fluke disease in cattle from Northeastern Argentina. Blood samples of 56 apparently healthy half-blood Brahman × Angus steers from slaughterhouses of enzootic areas of fasciolosis were collected and later analyzed. After death, from the total of animals, it was found that 29 harbored slight amount of fasciolas in the hepatic parenchyma. With conventional laboratory techniques, erythrogram, leukogram, proteinogram, and enzymogram (alkaline phosphatase, gamma-glutamyltransferase (GGT), and aspartate aminotransferase (AST)) were determined, as well as concentrations of iron, glucose, bilirubin, and prothrombin time. Parasitized animals revealed higher values for leukocytes, eosinophils, gamma globulins, and GGT activity when compared to controls (P < 0.05). Such parameters are inflammatory indicators attributable to an incipient cholangitis that characterizes the subclinical phase of distomatosis. Changes that may indicate cholestasis or liver dysfunction were not verified.